2005
DOI: 10.1111/j.1365-2435.2005.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Increase in the constitutive innate humoral immune system in Leach's Storm‐Petrel (Oceanodroma leucorhoa) chicks is negatively correlated with growth rate

Abstract: Summary1. Using a simple technique for assessing constitutive innate immune function recently adapted for use in wild populations, we characterize changes in avian immune system development by repeated measurements of individuals over the period of nestling growth in a wild population of Leach's Storm-Petrels ( Oceanodroma leucorhoa ). 2. We measured levels of natural antibodies (NAb) during the early, middle and late phases of storm-petrel development and related these levels and NAb rate of change to mass an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 58 publications
(78 reference statements)
3
76
0
Order By: Relevance
“…Namely, while fed (control) and Rt females did not differ in body mass, total body energy content, plasma proteins or corticosterone levels, Rt females showed significantly lower acquired immunity (IgY levels) but similar innate immunity (levels of NAbs) than control females. These results emphasize that variations in immune function do not seem to follow a simple energy allocation model in which the highest body masses would be associated with the highest immune responses (Mauck et al, 2005). Therefore, various branches of the immune system observed at one stage in an individual's life cycle may not necessarily reflect inherent quality differences between individuals when environmental conditions such as food availability vary.…”
Section: Discussionmentioning
confidence: 76%
“…Namely, while fed (control) and Rt females did not differ in body mass, total body energy content, plasma proteins or corticosterone levels, Rt females showed significantly lower acquired immunity (IgY levels) but similar innate immunity (levels of NAbs) than control females. These results emphasize that variations in immune function do not seem to follow a simple energy allocation model in which the highest body masses would be associated with the highest immune responses (Mauck et al, 2005). Therefore, various branches of the immune system observed at one stage in an individual's life cycle may not necessarily reflect inherent quality differences between individuals when environmental conditions such as food availability vary.…”
Section: Discussionmentioning
confidence: 76%
“…Buehler et al 2009a;Lee et al 2008), but significant relationships have been found with growth rate, mass differences among nestlings, prolonged fasting, body mass and environmental conditions in other species (e.g. Bourgeon et al 2010;Buehler et al 2009b;Mauck et al 2005;Parejo et al 2007). The fact that agglutination titres did not vary with the experimental treatments in our study suggests that NAbs are not (or only slightly) affected by environmental conditions in zebra finches or that the species actively buffers NAbs against stress-induced changes (see also Buehler et al 2009a), possibly at the expense of investment in other life-history traits.…”
Section: Discussionmentioning
confidence: 99%
“…Natural antibody and complement activity was quantified following the hemagglutination-hemolysis assay described by Matson et al (Matson et al, 2005) with modifications described by Mauck et al (Mauck et al, 2005). Hemagglutination and hemolysis titers were scored as the last titer at which the rabbit red blood cells were agglutinated or lysed.…”
Section: Complement and Natural Antibodiesmentioning
confidence: 99%